PENGARUH CORPORATE RISK DISCLOSURE TERHADAP NILAI PERUSAHAAN DAN VARIABLE GOOD CORPORATE GOVERNANCE SEBAGAI MODERASI - Nurmala Sari; Agus Seswandi; Rizqa Anita (Jurnal Daya Saing, 2025)
High company value will encourage the market to have confidence in the company's future potential and its current performance. The purpose of this study is to determine the factors that influence company value. The object of this research is all companies listed on the Indonesian Stock Exchange for two years, namely 2018 and 2019. The method used for sampling is purpose sampling based on predetermined criteria. The number of samples in this study was 442 with a total of 884 data. Testing analysis data is done by using the application software WarpPLS version 5.0. The results of the study showed that the corporate risk disclosure variable contributed positively by 5.6 % to the company's value. The good corporate governance variable strengthened the corporate risk disclosure variable which contributed positively by 0.2% to the company's value